The effect of large plastic deformation on elevated temperature mechanical behavior of dynamic strain aging Al-Mg alloys. (December 2019) - Meng, C.; Hu, W.; Sandlöbes, S.; Korte-Kerzel, S.; Gottstein, G.
Abstract: The tensile behavior at elevated temperature of heavily plastically deformed Al-Mg alloys with an Mg content of 1 to 5% was investigated. Large plastic deformation was imposed by confined channel die pressing at room temperature up to 18 passes. During heating to test temperature the specimens were observed to undergo recovery and partly recrystallization. The strain rate sensitivity was found to increase with increasing test temperature, and the previously reported asymmetry of the stress differential upon instantaneous up and down strain rate changes disappeared at elevated temperatures. The transition temperature from the low temperature to the high temperature behavior depended on the amount of pre-deformation. The observed phenomena were attributed to a change in deformation mechanism which occurred the earlier, i.e. at lower temperature, the higher the dislocation density introduced by pre-deformation. Graphical abstract: Image, graphical abstract